PREDICTING ECONOMIC INDICES OF VEHICLE INSURANCE USING THE “GREY-SYSTEM THEORY” - Kazimierz OPOKA (Scientific Journal of Silesian University of Technology. Series Transport)
This paper contains a prognosis of vehicle insurance economic indices using the Grey System Theory. It has been prepared based on data provided by a certain insurance company. The following economic factors were analysed: number of insured vehicles, premiums income, amount of damage cases covered, and value of paid compensations. The results of this study indicate a reduction in all analysed indices over twelve months.